Relationship between staff characteristics, motivation and financial incentive upon performance of maternal and child health workers in public health centres, Gianyar District - Oka Beratha; Ida Bagus Wirakusuma; I Gede Adnyana Sudibya (Universitas Udayana, 2013)
Maternal and child health (MCH) program plays a vital role in improving mother and child health. The success of such a program depends on the quality of service obtained from health care providers. The MCH program coverage in Gianyar District is still below the national target. This study aims to determine the relationship between staff characteristics, motivation and financial incentive upon the performance of MCH workers in public health care centres. The study design was cross-sectional with sample of 70 people. Samples were selected using a systematic random sampling. The independent variables were age, duration of employment, education, training, motivation and financial incentive while the dependent variable was the official performance. Data was collected using interview and observation. Data were analysed using univariate, bivariate (chi-square) and multivariate (logistic regression) analysis. The majority of respondents 41 (58.6%) were lower age, shorter tenure 39 (55.7%), college-educated 57 (81.4%), 36 (51.4%) had received training, 42 (60.0%) of participants demonstrated low motivation, 47 (60.7%) were influenced by amount of financial incentives and high performance staff is only 40 (57.1%). From the bivariate analysis, there was a significant association between training [OR=2.88; 95%CI: 1.08-7.67], motivation [OR=6.77; 95%CI: 2.15-21.29] and financial incentives [OR=4.09; 95%CI: 1.30-12.85] and staff performance. From the multivariate analysis, only training [OR=6.11; 95%CI: 1.61-23.23], motivation [OR=7.48; 95%CI: 1.81-30.93] and financial incentives [OR=5.09; 95%CI: 1.12-23.21) were found to have significant association. Based on study findings, there is a need to increase incentive and further staff training to increase staff motivation to improve the overall performance output.